Liver Toxicity with Cancer Checkpoint Inhibitor Therapy - Nadeau, Brian A.; Fecher, Leslie A.; Owens, Scott R.; Razumilava, Nataliya (Seminars in Liver Disease, 2018)
Immune checkpoint inhibition targeted against cytotoxic T-lymphocyte–associated antigen 4 (CTLA-4) and programmed cell death protein 1 (PD-1) has shown clinically significant survival benefit when used to treat multiple types of advanced cancer. These drugs have gained approval by the US Food and Drug Administration and their indications continue to increase. Checkpoint inhibitor therapy is associated with a unique side-effect profile characterized as immune-related adverse events (irAEs), which can result in significant morbidity and rarely mortality. Hepatotoxicity from checkpoint inhibitors is a less common irAE and often mild, while its incidence and severity vary based on the class and dose of checkpoint inhibitor, monotherapy versus combination therapy, and the type of cancer. Histological assessment of suspected irAEs is nonspecific and can show a variety of features. Hepatic irAEs can require discontinuation of checkpoint inhibitor therapy and treatment with immunosuppressive agents.
Keywords: hepatotoxicity; immune-related adverse events; checkpoint inhibitor; CTLA-4; programmed cell death protein 1